(untitled) (Annals of Medical Research, 2021)
Aim: To compare the results of isolated aortic valve replacement through ministernotomy and full sternotomy in the elderly.Material and Methods: This single-center prospective study includes patients over 60 years of age who undergone isolated aortic valve replacement either by upper ministernotomy (22 patients) or full sternotomy (22 patients) during 5 years. Both groups were followed 12 months postoperatively.Results: All preoperative and operative measures were similar. However, the ministernotomy group had an average of 3 hours less mechanical ventilation time (p0.001), 200 ml less bleeding (p0.001), 1.5 days shorter hospital stay (p=0.002), and 4 days less analgesic use (p=0.001). Postoperative wound infection (18.2%), sternal detachment (9.1%) and pericardial effusion (4.1%) were seen only in the full sternotomy group.Conclusion: The advantages of ministernotomy are more prominent during recovery period in elderly patients.